Myrtenal mitigates streptozotocin-induced spatial memory deficit via improving oxido inflammatory, cholinergic and neurotransmitter functions in mice - Isaac Oluwatobi Akefe; Victoria Aderonke Adegoke; Ibrahim Yusuf Lamidi; Matthew Phillip Ameh; Enokela Shaibu Idoga; Simon Azubuike Ubah; Itopa Etudaye Ajayi (Elsevier, 2022)
The occurrence of chronic neurodegenerative disorders is on the rise, but with no effective treatment due to the paucity of information on the pathological mechanism underlying these disorders. Thus, this study investigated the role of oral administration of myrtenal in mitigating memory deficits and neuro-biochemical alterations in streptozotocin-demented mice model. Mice (n ​= ​35) were randomly allocated into five cohorts consisting of 7 mice each; Group I: Control mice received vehicle alone; Group II: streptozotocin; Group III: streptozotocin + 100 ​mg/kg myrtenal; Group IV: streptozotocin +200 ​mg/kg myrtenal; and Group V: streptozotocin ​+ ​donepezil 0.5 ​mg/kg. Data from this study demonstrated that the administration of streptozotocin (STZ) impaired spatial memory and induced alterations in markers of oxido-inflammatory response, cholinergic function, cytoarchitecture, and neurotransmitter levels in mice hippocampus. Notably, administration of myrtenal enhanced spatial memory performance in STZ-demented mice by improving the activities of endogenous antioxidant enzymes to protect the brain from oxido-inflammatory stress. Treatment with myrtenal also restored cholinergic function and stabilized the homeostasis of neurotransmitters in STZ-demented mice. The authors infer that fruits rich in myrtenal may be beneficial for treating patients living with dementia associated with Alzheimer's disease.